THE ROLE OF NEW ENVIRONMENTAL PARADIGM IN SWITCHING INTENTION TO ELECTRIC VEHICLES: A VALUE BELIEF NORM PERSPECTIVE - Panjaitan, Donna; Rinawati Simanjuntak, Evi (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This research arises from the rapid introduction of electric vehicles (EVs) in response to sustainability concerns. Many studies have analyzed the switching intention mechanism from the utilitarian perspective. However, fewer studies address EV adoption from a psychological standpoint. Using the Value Belief Norm framework, this study investigates the psychological values influencing an individual's intention to switch from conventional to electric vehicles driven by their norms. This research uses a quantitative approach, using a survey method. Using convenience sampling, we gathered 294 usable responses. Data was analyzed using the Partial Least Squares Structural Equation Model (PLS-SEM). The results show that individuals with a New Environmental Paradigm (NEP) will be more aware of environmental problems. NEP, as a customer value, drives individuals’ belief that there is an ecological problem. NEP also drives self-efficacy in understanding environmental issues. Data support that problem awareness and self-efficacy will form personal norms that, in turn, will create the intention to switch to electric vehicles. This research provides theoretical implications by highlighting individuals' switching intentions to use electric vehicles, reflecting social transformation and commitment to sustainable practices. The value-belief-norm (VBN) Theory suggests that individual, exceptionally altruistic values play a significant role in pro-environmental behaviors such as using electric vehicles.